Developmental grading of female reproductive system of Chrysoperla sinica (Tjeder) and its application to forecasting in the field - XU Yong-yu; HU Cui; MOU Ji-yuan (浙江大学学报. 农业与生命科学版, 2000)
The female reproductive system of Chrysoperla sinica was divided into 5 developmental grades according to its anatomic characteristics, and this was verified by the analytical results of the biochemical compositions including nucleic acid, protein, phospholipid etc. in the different gradational ovaries. The studies of the relationship between the quantitative changes of the ovary in the 5 different grades and the numbers of the egg produced in the field showed that the egg production reached the peak period after 3-4 days when the number of the female adult at the 3 rd grade made up above 50 percent of the total number found, and it reached the final period when the number of the female adult at the 4th grade made up above 50 percent.